Barriers in Achieving Social Cohesion: A Qualitative Study - Edip Aygüler; Sema Buz; Bekir Güzel (Journal of Economy Culture and Society)
Turkey currently has a large number of asylum applications from asylum seekers demanding international protection and expecting to move on to third countries. The number of asylum seekers in Turkey increased dramatically following the mass immigration of refugees from Syria in 2011. This situation has led to some conflicts between the local community members and asylum seekers. It has become evident that all asylum seekers under international protection status and local community members should develop a mutual social cohesion process. To understand how to make social cohesion more successful and to reveal the deficiencies in existing social cohesion activities, semi-structured, in-depth interviews were conducted with 17 NGO professionals and 15 non-Syrian asylum seekers. Taking a phenomenological approach, the resulting interview data were analyzed using the MAXQDA 12 program. Four themes emerged: (1) how participants define social cohesion; (2) how the insufficiency/deficiency of existing social cohesion activities affect social cohesion; (3) local community member factors that hinder social cohesion; and (4) asylum seeker factors that hinder social cohesion. The results suggest that, in order for social cohesion efforts to succeed, comprehensive cohesion policies must be developed and cooperation among stakeholders must be increased. It was observed that it is important that social cohesion activities are conducted with the equal participation of all parties, they are constructed on similarities across the groups, and planned in such a way that prejudices are reduced and cohesive neighborhood living is realized.